CLASSICAL AND QUANTUM SOURCES OF RANDOMNESS. - Kuś, Marek (Poznan Studies in the Philosophy of the Sciences & the Humanities, 2015)
Is there a place for genuine randomness in nature, independent of our possibilities and limitations in acquiring knowledge about the external world? Or in other words, what is the ontological status of randomness and probability? The problem has been present in philosophy nearly since its advent. Not astonishingly, no satisfactory answer has been proposed, the problem recurs in different forms and gains new insights in the course of the development of physical sciences. Undoubtedly, quantum mechanics gave a revolutionary turn to the issue. What is even more interesting, it constantly provokes new problems. It is thus worth returning to the basic questions of the nature of randomness in the light of recent developments of quantum theory and increasing experimental possibilities to check its predictions. Here I want to compare the possibilities given by classical and quantum physics to accommodate and prove the existence of 'genuine randomness' and discuss recent results concerning 'amplification of randomness', showing how quantum physics 'outperforms' classical mechanics in approaching an ultimate goal of exhibiting 'truly random process'.